2019
DOI: 10.1088/1361-6641/aaf820
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of enhanced photocatalytic activity of Cr-doped ZnO nanoparticles revealed by photoluminescence emission and electron spin resonance

Abstract: In this work, we successfully synthesized Cr 3+ doped ZnO nanoparticles using a sol-gel method, and elucidated how Cr 3+ dopant is critical for enhancing photocatalytic activity. The nature of the point defect analyzed by electron spin resonance (ESR), and photoluminescence (PL) emission revealed the role of the Cr 3+ dopant. When introducing Cr 3+ ions in ZnO, the PL emission intensity decreased, indicating a reduction of the radiative recombination rate due to the heterojunction formation between the dopant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 55 publications
3
14
0
2
Order By: Relevance
“…The Zn1-xCuxO samples with x = 0.0 and 0.01 were prepared by sol-gel method similar to previous reports [10,11]. Typically, the zincnitratehexahydrate -Zn(NO3)2.6H2O (Sigma-Aldrich) and copper(II) nitrate trihydrate -Cu(NO 3 )2.3H2O (Sigma-Aldrich) were mixed with citric acid -C6H8O7.H2O 1M (Sigma-Aldrich) with a molar ratio of metal ions : acid = 1:3.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Zn1-xCuxO samples with x = 0.0 and 0.01 were prepared by sol-gel method similar to previous reports [10,11]. Typically, the zincnitratehexahydrate -Zn(NO3)2.6H2O (Sigma-Aldrich) and copper(II) nitrate trihydrate -Cu(NO 3 )2.3H2O (Sigma-Aldrich) were mixed with citric acid -C6H8O7.H2O 1M (Sigma-Aldrich) with a molar ratio of metal ions : acid = 1:3.…”
Section: Methodsmentioning
confidence: 99%
“…After 150 min of exposure to visible light, the MB degradation efficiencies were about 54.95 % and 76.65 % for ZnO and ZnO:Cu, respectively. The doping effect on the enhanced photocatalytic activity could be from various reasons such as ZnO bandgap reduction [19], enhanced light absorption [20], and excited carriers separation [11] which all affect photoelectron-hole generation/recombination processes.…”
Section: Photocatalytic Activity Experimentsmentioning
confidence: 99%
“…Organic ingredients in textile wastewater are very difficult to biodegrade and toxic to the environment [1]. Consequently, scientists around the world are studying to find ways to handle organic components in wastewater [2]. TiO2 nanomaterials with tubular structure (TNT) have shown superiority in the treatment of textile wastewater by photocatalytic ability [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the natural sunlight, there is a small amount of UV-light ~3%. Hence the bandgap engineering of ZnO has been intensively investigated such as doping ZnO with other elements [5][6][7][8][9], coating ZnO with other materials [10,11]. Recently, S. Choi et al [7] found that when ZnO doped with transition metal ion Cu 2+ , the photocatalytic activity of ZnO was improved thanks to the separation of the excited carrier.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, S. Choi et al [7] found that when ZnO doped with transition metal ion Cu 2+ , the photocatalytic activity of ZnO was improved thanks to the separation of the excited carrier. Recently, we have shown that the Cr 3+ could be play as an electron trap center in the hydrothermal ZnO doped Cr samples [5]. It means that the photoelectrons were trapped then would leave holes without recombination.…”
Section: Introductionmentioning
confidence: 99%